Variables Related to Human Breast Cancer. - Anderson, V. Elving (University of Minnesota Press, 1958)
Variables Related to Human Breast Cancer was first published in 1958. The question of what role, if any, heredity plays in the etiology of human cancer is of obvious importance in the continuing search for an answer to the riddle of cancer. This book describes a study which was conducted at the Dight Institute for Human Genetics of the University of Minnesota, seeking evidence on two aspects of the heredity question. The objectives were, first, to determine whether there is an increased frequency of cancer among relatives of breast cancer patients (over what would be expected by coincidence) a.